Локальність та перманентність стану постмодерну - Патерикіна, В.В. (Культура народов Причерноморья, 2013)
Філософська та культурологічна думка продовжують дослідження ситуації постмодерну, хоча відчувається певна втома від цього терміну та від змісту, який він означає. Початок ситуації постмодерну можна вважати із завершенням модерну, але якщо зважати на постійне оновлення суспільства та зміну парадигм, то до постмодерну можна ставитись як до перманентного стану у культурі людства. Локальність постмодерну пропонується визначати як період кінця ХХ-го - початку ХХІ-го століття, а перманентність постмодерну розглядати як постійний супутник культури людства. Философская и культурологическая мысль продолжают исследование ситуации постмодерна, хотя ощущается определённая усталость и от этого термина и от содержания, которое он означает. Начало ситуации постмодерна начинается с завершением модерна, но если учитывать постоянное обновление общества и смену парадигм, то к постмодерну можно относиться как к перманентному состоянию в культуре человечества. Локальность постмодерна предлагается определять как период конца ХХ-го - начала ХХІ-го столетия, а перманентность постмодерна рассматривать как постоянный спутник культуры человечества. Any cultural epoch doesn't exist in a clear form; an exception is made by single examples of spiritual breaks. Multiple local situations which it is possible to call post-modernist are observed in the history of mankind. In a context of continuous updating of cultural stages the postmodern can be carried to the civilization beginning. Without having the similar name, post-modernist ideas directed people throughout visible history. As a phenomenon a postmodern not new in spiritual practice of mankind and it is always existed as an attitude, and not just on a change of eras. Nowadays have two categories: coincidence to the requirement of time and philosophical filling of a modernist style. Linearly - forward development without repeating is defined as a modernist style. The prefix "post" creates a new cultural paradigm though the postmodern isn't identified with the period which comes after a modernist style. It is possible that the postmodern will be the fourth era after Antiquity, the Middle Ages, New time. It is always will be something new in the history of cultural development; therefore the ideology of a postmodern will accompany mankind history.